Pico Hydro Generator Module for Domestic Water Pipe Fitting - Abdul Wahab, Muhammad Hifzhan; Kok Boon Ching (Evolution in Electrical and Electronic Engineering, 2022)
Residents with B40 status, especially residents who have private homes, need a low cost of living and save money. To get electricity savings, an innovation can be done. The existence of water pipe flow in residential areas that is constantly flowing all the time can be used to be converted to electricity using hydro pico generator module for domestic water pipe installation so that it can be used to supply electricity to consumers. The output stability of the pico hydro generator module can be enhanced with a stabilizer in the form of a DC to DC converter system so that it can reach a stable voltage of 5 volts DC. In this final project, the DC to DC converter used is a buck-boost converter obtained from a permanent magnet DC generator in a pico hydro generator module system. The buck-boost converter circuit can produce a stable output voltage of 5 volts DC. A stable DC output voltage is then routed to the battery charger module with a frequency of 50 Hz. A predefined buck-boost converter circuit can work when given an input voltage between 2-8 volts. The test results of the whole system produced an average output voltage of 4.98 until 5.12 volts with an average output current of 0.12 amperes.